Grasping with contacting each finger simultaneously by the robot hand equipped with optical proximity sensors on fingertips (Estimation of reflectance of the object surface and calibration the sensor output) - Keisuke KOYAMA; Yosuke SUZUKI; Aiguo MING; Makoto SHIMOJO (Nihon Kikai Gakkai ronbunshu, 2015)
In grasping of a robot hand, a contact timing of each finger has a influence on grasp success. In order to eliminate the gap and grasp an object quickly, proximity sensing from the robot surface is effective way. The sensor detects the object posture and distance in a several tens of millimeters from the robot surface. It enables that the robot adjusts postures and distance between the object and fingertips along the object surface. In this paper, we demonstrate a quick grasp with contacting each finger simultaneously by proximity sensors on fingertips. In order to realize the grasp by optical proximity sensors, we introduce our reflectance estimation of the object surface and calibration of the sensor output. This approach uses only the proximity sensor output and a relative moving distance of the fingertip. It is unnecessary to add extra equipment or sensor for estimation and calibration. It is possible to achieve the grasp regardless of the reflectance of the object surface. In the experiment, we confirmed that the approach can be applied to surface with different reflection characteristics (iron plate, aluminum plate, paper: cylinder and plane ), and the hand can grasp a object with various reflectance surfaces (31.9∼76.1%) quickly with contacting each fingertip within 0.056s.